Detection of treponemes in digital dermatitis lesions of captive European bison (Bison bonasus). - Stefan Hoby (Public Library of Science (PLoS), 2021)
A newly-discovered foot disease of unknown origin in captive European Bison (Bison bonasus) was recently detected at Berne Animal Park. Dermatitis of the interdigital cleft of varying degrees of severity was diagnosed in all animals (n = 10). The aim of this study was to describe the gross and histological lesions of the interdigital cleft found in 10 captive European bison and to identify involved potential pathogens in affected feet using molecular-based methods for Treponema spp., Dichelobacter nodosus and Fusobacterium necrophorum. Lesions were scored according to the degree of gross pathology at limb level. In a single animal, the gross lesions were restricted to focal lesions on the dorsal aspect of the digital skin of each foot (score 1), whereas all other animals showed at least one foot with extended lesions including the interdigital cleft (score 2). The presence of viable spirochaetes was observed in all animals using dark field microscopy. Applying fluorescence in situ hybridisation (FISH) on biopsies, Treponema spp. were identified, infiltrating the skin lesions in varying numbers in nine animals. Nested PCRs for Treponema medium, Treponema phagedenis and Treponema pedis of swab samples showed three positive animals out of ten for the latter two, whereas pooled biopsy samples were positive in all ten animals for at least T. phagedenis (9/10) and/or T. pedis (7/10), while all samples were negative for T. medium. However, none of these Treponema species could be isolated and sequence analysis of the amplified products showed 100% match of 365 base pairs (bp) to Treponema phylotype PT3 and almost full match (530 of 532 bp, 99.6%) to Treponema phylotype PT13. The presence of T. phagedenis, PT3 and PT13 phylotypes was confirmed by FISH analyses. The phylotypes of T. phagedenis were present in all hybridized positive biopsies of Treponema spp., and PT13 and PT3 were less abundant. Neither D. nodosus nor F. necrophorum were detected. The histological Treponema score was mostly mild. Digital dermatitis in captive European Bison is contagious and differs from bovine digital dermatitis, concerning associated pathogens as well as gross appearance.